Wild Performatives: experiments in rewilding at the Knepp Wildland Project - Overend, D; Lorimer, J (Routledge, 2018)
This article reflects on a two-day creative workshop at Knepp Castle Estate in October 2017. Knepp is the location of a large-scale ‘rewilding’ project established in 2002, which uses free-roaming herbivores to cultivate habitat change and restore natural processes. Using collaborative performance-making strategies, participants attempted to respond and contribute to the complex ecology of the site, exploring the potential for productive exchanges between human and nonhuman actors. The article focusses on a series of ‘wild performatives’ that occurred during the event. Focussing on three applications of this concept, it explores a range of affective encounters with the ecologies, practices and concepts of rewilding.